Vous êtes sur la page 1sur 2

stsm-usthb.blogspot.

com

Exercice 1
assume(real)
  = real   
~ 2 ~ −4 ~ 4
V1 = ; V2 = ; V3 =
2 0 −2
     
~=V ~1 + V~2 = −2 ~ =V ~3 − V ~2 = 8 ~ =V ~1 − V
~ 2 + 2V ~3 = 14
A ; B ;C
2 −2 −2
Exercice
 2     
3 2 −1
~1 =  −2 ; V
V ~2 =  −4 ; V ~3 =  2 
1 −3 2
q
~ 2 2 2
a. Module A = Ax + Ay + Az
√ √
~ ~ ~
V1 = 14 = 3. 74; V 2 = 29 = 5. 39; V 3 = 3
2  2
4 √
~=V
A ~1 + V~2 + V ~3 , A~ =  −4 ; A~
= 32 = 5. 66
2
0
 
5 √
~ = 2V
B ~1 − 3V ~ 2 − 5V~3 ; B~ =  −2 ; B ~ = 30 = 5. 48
1 2

~1 · V~2 = ~1 ~ ~1 ·V
V ~2
b. Angles : On utilise V V V 2 cos (α) ⇒ cos (α) = V
k ~1 kkV~2 k
~1 · V
V ~2 = 11; cos (α) = √ 11√ = 0.545 92 ⇒ α = ±56.91◦
14 29
~1 · V
V ~3 = −5; cos (α) = √ −5
= −0.445 44 ⇒ α = ±63. 55◦
3 14
~2 · V
V ~3 = −16; cos (α) = −16√ = −0.990 38 ⇒ α = ±7.96◦
3 29
Exercice 3
~ ~
 V1 · V2 = 
On utilise 0 
2 4
~ 1 =  a ; V
V ~2 =  −2 ; Donc V ~1 · V~2 == 6 − 2a = 0 ⇒ a = 3
1 −2
Exercice 4
Evident
Exercice 5
Méthode 1       
~1 × V
V ~2 = 2~i + 2~j × −4~i = −8 ~i × ~i − 8 ~j × ~i = ~0 + 8~k
       
~1 × V
V ~3 = 2~i + 2~j × 4~i − 2~j = −4 ~i × ~j + 8 ~j × ~i = −12~k
     
~2 × V
V ~3 = −4~i × 4~i − 2~j = 8 ~i × ~j = 8~k
Méthode
 2    
2 −4 4
~1 =  2 ; V
V ~2 =  0 ; V ~3 =  −2 
0 0 0
~i ~j ~k
 

2 0

2 0

2 2
0
~1 × V~2 = 2 2 0 = ~i ~ ~ ~  0 

V 0 0 − j −4 0 + k −4 0 = 8k =


−4 0 0 8
~i ~j ~k
 

2 0

2 0

2 2
0
~1 × V~3 = 2 2 0 = ~i ~ ~ ~  0 

V −2 0 − j 4 0 + k 4 −2 = −12k =


4 −2 0 −12
~j ~k

~i
 
0
~2 × V~3 = −4 0 0 = ~i 0 0 − ~j 2 0 + ~k −4 0 = 8~k =  0 

V −2 0 4 0 4 −2
4 −2 0 8
Exercice 6
1
     
3 2 1
~1 =  −1 ; V
V ~ 2 =  1 ; V ~3 =  −2 
2 −1 2   
    24   15  
~1 × V
V ~2 · V~3 = −5; V ~1 × V ~2 × V ~3 =  7 ; V ~1 × V ~2 × V~3 =  15 ; V ~1 × V~2 · V
~3 = V ec × (scal) =
  −5 −15
impossible; V ~1 · V ~2 × V~3 = −5
 
    3
~1 · V
V ~2 · V~3 = (scal) · vect = impossible (mais V ~1 · V
~2 V ~3 =  −6 );
6
 
          2
~1 + V
V ~2 × V ~1 − V ~2 = − V ~1 × V ~2 + V~2 × V
~1 = −2 V ~1 × V~2 =  −14 
−10
Exercice 7
assume(real) =real 
−e−t
     
sin t exp (−t) cos t
~1 =  cos t ; V
V ~2 =  2 cos (3t)  ⇒ dV~1 =  − sin t ; dV~2 =  −6 sin 3t 
dt dt
t √ 2 sin (3t) 1 6 cos 3t
dV~1 dV~2
dt = 0; dt = 36 + e−2t